Pelatihan seni musik Tradisi Gamelan Tokol pada generasi muda - Hary Murcahyanto (Universitas Hamzanwadi, 2022)
Traditional music is one of the characteristics of an area that needs to be preserved. The traditional music of the Gamelan Tokol is starting to become less attractive to the younger generation due to the need for more socialization, training, and platforms for performing their works so that the younger generation's creativity in developing traditional music begins to wane. In addition, there is a need for the notation of traditional pieces that have never been written in notation form. This activity aims to realize conservation efforts, creativity, and regeneration of traditional Gamelan Tokol music. The mentoring activities will be carried out from May to July 2022 at the Tunggal Galih art studio, Denggen Village, Selong District. This activity was attended by 43 youth arts activists from areas around the Selong sub-district and assisted by ten students. The result of this activity is the existence of traditional Gamelan Tokol music training activities, contributing to the younger generation in terms of creativity in playing patterns using notation so that a new generation is formed, which is the previous regeneration as an embodiment of efforts to preserve traditional music in the younger generation.